Waktu Kering Angin Pada Daun dan Tangkai Terhadap Mutu dan Rendemen Minyak Nilam Aceh (Pogostemon cablin Benth) - Nuwa Nuwa (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
Study of the yield and quality of Aceh patchouli oil from leaves and stalks at several drying times, in Bukit Batu, Palangka Raya City, Central Kalimantan. Treatment of drying time patchouli leaves and stalks to a certain extent can increase the yield of patchouli oil produced. 4 days drying treatment leaves produced the highest yield of 5.17%, stalks for 8 days produced the highest yield of 3.78% decreasing with the longer drying time. The lowest yields without desiccation (control) on leaves and stalks were 1.4% and 1.16%. Drying time treatment of patchouli leaves and stalks to some extent increased the patchouly alcohol content of patchouli oil produced. Drying time treatment for 8 days produced the highest patchouly alcohol in leaves (31.48%) and stalks (29.71%) then decreased with the longer drying time. The lowest patchouly alcohol content in the control treatment 22.94% and 19.73% in the leaves and stalks. Physical and chemical properties of patchouli oil characteristics (color, optical rotation, specific gravity, refractive index and patchouly alcohol), that the quality of patchouli oil produced by the control is low. Quality requirements of patchouli oil based on SNI No. 06-2385-1991